2018
DOI: 10.1093/chromsci/bmy075
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Determination of Selected Polyphenols from Medicinal Plants

Abstract: A study of the simultaneous separation and determination of selected polyphenols (rutin, narirutin, naringin, hesperidin, neohesperidin, quercetin, naringenin, kaempferol and hesperetin) with reported effects in the treatment of depression and cardiac and neurodegenerative diseases was performed. An RP-ultrahigh-performance liquid chromatography (UHPLC)-ultraviolet method for analyte separation and determination was successfully developed and validated for a ZORBAX Eclipse Plus C18 RRHD analytical column. Sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Besides fruits, hesperidin is available in other parts of the citrus plant, such as leaves, with higher and remarkable concentration in young leaves (about 50% the concentration found in the fruit's albedo) [20]. Hesperidin occurs in notable concentrations in several plants other than citrus, including certain officinal plants, such as Menthae piperitae, Hypericum perforatum and Salvia officinalis, although less abundant than other flavonoids such as rutin [25]. In the case of Menthae piperitae, a wide range of levels was observed, depending on the varieties and growing sites, such as up to 2.15 mg/g (dry weight) [26], and up to 13.1 mg/g (dry weight) [27].…”
Section: Sources Of Hesperidinmentioning
confidence: 99%
“…Besides fruits, hesperidin is available in other parts of the citrus plant, such as leaves, with higher and remarkable concentration in young leaves (about 50% the concentration found in the fruit's albedo) [20]. Hesperidin occurs in notable concentrations in several plants other than citrus, including certain officinal plants, such as Menthae piperitae, Hypericum perforatum and Salvia officinalis, although less abundant than other flavonoids such as rutin [25]. In the case of Menthae piperitae, a wide range of levels was observed, depending on the varieties and growing sites, such as up to 2.15 mg/g (dry weight) [26], and up to 13.1 mg/g (dry weight) [27].…”
Section: Sources Of Hesperidinmentioning
confidence: 99%
“…The samples under investigations are citrus fruits and juices, 24,25,[26][27][28][29][30][31][32] plasma, 33,34,35 pharmaceuticals 36,37 and medicinal plants. 38 The main disadvantages of chromatographic methods are tedious procedure including preliminary extraction and preconcentration of the analyte, expensive instruments and solvents of high purity. Analytical characteristics and selectivity of naringin electrochemical determination can be further improved.…”
mentioning
confidence: 99%
“…Reported results were in agreement with those of Sekeroglu et al [ 32 ], who observed higher polyphenol concentrations in H. perforatum flowers and leaves with respect to stem aqueous extracts. According to the literature, in H. perforatum the most abundant phenolic compounds showing biological activity are flavonoids, such as quercetin, rutin, kaempferol and naringenin, and phenolic acids, like chlorogenic, gallic, caffeic, ferulic and vanillic acids [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%